ANALISIS KEBIJAKAN PENCEGAHAN DAN PENANGGULANGAN STUNTING DI INDONESIA: Dengan Pendekatan What Is The Problem Represented To Be? - Made Agus Sugianto (CV ODIS, 2021)
This study analyzes policies on the prevention and control of stunting in Indonesia with the approach